Morphological Identification Warehouse Pests as a Teaching Media for Plant Protection Practicals - Annisa' khurun ain fauziah; Susanti, Ambar; Faizah, Mazidatul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The purpose of the study was to determine the warehouse pest type bruchus that attacks green bean commodities in storage areas at the Kolakan market in Jombang Regency. The research period began in May - September 2023, located at the Agricultural Laboratory of the Faculty of Agriculture, KH University. A. Wahab Hasbullah Jombang. Mung bean seed samples were taken from the storage warehouse at the Kolakan Market in Jombang Regency. The research method used is the descriptive method used to identify warehouse pests that attack green bean seeds. While this type of research is qualitative. It is known that Callosobruchus maculatus is a warehouse pest that can complete its life cycle actively in green bean storage areas. Its distribution is higher in food ingredients in storage areas. This is expected to be used as a teaching medium in the identification of warehouse pest morphology in the practical of Plant Protection. Keywords: identification; Instructional media; Warehouse Pests; Mung Beans